Closed Reduction of Bilateral Posterior Shoulder Dislocation with Medium Impression Defect of the Humeral Head: A Case Report and Review of Its Treatment - Soorena Rezazadeh; Amir Reza Vosoughi (Case Reports in Medicine)
Bilateral dislocation of the shoulder is a rare injury. The main causes are electrical shock, extreme trauma, and epilepsy. A 25-year-old athletic-body man had sustained bilateral shoulder pain and restricted external rotation following electrical shock for five days. Although articular surface damage was about 50% in the right side and 30% in the left, it could be managed successfully by close reduction without pinning. During one-year follow-up, no recurrent dislocation or limitation of motion was seen. Closed management of medium size defect of the humeral head after posterior dislocation can be performed in cooperative and especially muscular patients.